EIBIS 2020 - EU overview - European Investment Bank (2020)
The EIB Investment Survey gathers unique insights on the corporate investment landscape in the European Union. It is an essential tool that outlines companies' needs for finance and the constraints that prevent them from making investments. The 2020 edition shows the effects of the COVID-19 crisis on companies' investment plans and highlights how European firms are investing in digital technology. Another focus is dedicated to how businesses will handle climate change and the transition to a low-carbon future. The survey is based on 12 000 companies across the 27 European Union countries, and it includes a benchmark sample in the United Kingdom and United States. This overview provides the 2020 results for EU.